Tendenzen und Probleme der neueren Partikel-Forschung - Helbig, Gerhard (Studia Germanica Posnaniensia, 2018)
In confrontation with a variety of theoretical conceptions and methods of description of particles the author tries to l. clearly determine the specificity of particles and criteria of their distinction, 2. specify them, 3. answer to a theoretical question: general meaning (Gesamtbedeutung) - and differentiated function variants (e. g. doch1, doch2, doch3 etc.)